ANALISIS KEBUTUHAN TENAGA KERJA BERDASARKAN BEBAN KERJA METODE WORKLOAD INDICATOR STAFFING NEED DI RSIA RUMKITBAN MALANG: Analysis of Labor Needs Based on Workload Indicator Staffing Need Method in Rumkitban MCH Malang - Lilik Afifah; Retno Dewi Prisusanti; Fita Rusdian Ikawati (Forind Press, 2023)
Management of medical records in hospitals is to support the achievement of orderly administration in order to achieve hospital goals, namely improving the quality of health services in hospitals. One important element to support effectiveness and efficiency in managing medical records is the human resources aspect. The phenomenon that exists in an institution is not only a lack of workforce, but there can also be a buildup of staff in one installation without clear work. Therefore, it is necessary to make efforts to calculate the workforce requirements in an agency by calculating the existing workload. One of the obstacles to registration is the limited number of personnel. Based on a survey, the number of employees in the medical records installation is 25 people. Where the available working time is 281 days/year or 118,200 minutes/year. The aim of this research is to find out more clearly how to calculate workforce needs using the workload indicator staffing need (WISN) method at the medical records installation at the COVID 19 referral hospital RSIA Rumkitban 05.08.02 Malang. This type of research is a quantitative research approach with a descriptive study design. The results of research using the WISN method estimate that 2 medical records personnel in the TPPRI section are needed, and human resources are also needed to change shifts. There is a shortage of medical records personnel in the TPPRI section at RSIA Rumkitban because from the calculation results an additional 2 people are needed and currently only 2 medical records personnel are available.